SEDIMENTOLOGICAL SIGNIFICANTS OF DEEP-WATER SEDIMENTS OF PENOSOGAN FORMATION IN KEBUMEN AREA, CENTRAL JAVA - Vicky, Widianto (Departmen Teknik Geologi, 2015)
Deep-water sediments are commonly associated with turbidity current, results variety of physical sedimentary features. They are currently a major focus of both academic research and industrial interest related to petroleum play. Several reservoirs in Indonesia’s basin belonged to deep-water products. Comprehensive geological study with good basic sedimentology knowledge is needed to understand more about deep-water sediments related to reservoir opportunities. Penosogan Formation, a part of South Serayu Basin, is one of good outcrop data which can be used as a guide to distribute analogue in subsurface geophysical data. This paper objective is to understand better the heterogenetic deep-water sediments facies by using outcrops approach, then the conceptual of reservoir characteristic could be identified. The data were collected in the Penusupan area, Kebumen – Central Java. The primary methods used in this study were stratigraphic measuring section and field geological mapping. Laboratory analyses were also added to support the study. Based on integration of paleontology, petrography, and facies interpretation, Penosogan Formation in study area demonstrate turbidity current products which are divided into three lithofacies association, namely: very coarse grained facies, coarse grained facies and fine grained facies. These association represent prograding features from outer fan into middle fan. The outer fan facies is characterized by interbedded very fine – fine grained sandstone with shale (approximately 25 meters), sand-shale estimation + 40 % net to gross ratio, porosity (Φ) up to 8,4 %, and permeability up to 129,38 mD. The middle fan is characterized by interbedded medium – coarse grained sandstone and thin layered shale with pebble to boulder conglomerate (approximately 46 meters), sand-shale estimation + 85 % net to gross ratio, porosity (Φ) up to 9,5 %, and permeability up to 146,55 mD.